From Content Creators to Zakat Payers: The Fatwa of Indonesian Ulema Council and the Rise of Digital Fiqh - Kurniawan, Edi; Ahmad, Humaira; Muhamad Zaenal Muttaqin (Islamic Law and Social Issues in Society, 2025)
This article examines the juridical transformation of digital content creators into zakat payers within the framework of contemporary Islamic law. The rapid expansion of Indonesia’s digital creative economy, with professions such as YouTubers and Instagram celebrities earning substantial yet fluctuating incomes, raises urgent questions regarding the applicability of classical zakat provisions to modern revenue models. Therefore, this article critically analyzes the Indonesian Ulema Council (MUI) Fatwa No. 1 of 2024 on Zakat for Digital Content Creators, issued during the 8th National Fatwa Commission Conference. Using a juridical-normative method combined with content analysis, this article examines fatwa texts, Qur’anic and hadith foundations, and both classical and contemporary fiqh perspectives, triangulated with recent literature on Islamic law in the digital economy. The findings demonstrate that the fatwa categorizes creators’ income as māl mustafād (acquired wealth) subject to zakat once it reaches the niṣāb equivalent of 85 grams of gold, with rates of 2.5% (lunar year) or 2.57% (solar year). Its flexibility in permitting zakat payment upon receipt of income, without waiting for a full ḥawl, reflects Islamic law’s responsiveness to irregular digital earnings. This article concludes that the fatwa not only regulates wealth redistribution (ḥifẓ al-māl) and reinforces ethical content production (ḥifẓ al-dīn), but also marks a significant step in the rise of digital fiqh. Its key contribution lies in proposing a practical zakat calculation model for multi-source digital income while highlighting taysīr (facilitation) and rafʿ al-ḥaraj (removal of hardship) as normative foundations for Shariah adaptation in the digital economy.